Model Pembelajaran di Rencana Pelaksanaan Pembelajaran Mata Pelajaran Informatika - Nora Triningsih (Cakrawala: Jurnal Pendidikan, 2022)
This study aims to determine how effective and innovative models are applied in informatics subjects. The learning model that can be applied to actively involve students in the teaching and learning process is to use a cooperative learning model because with cooperative learning there is interaction between students with one another. The learning approach has many definitions, but each one still has a relationship. There are 3 approaches to learning philosophy, namely: idealism, realism, pragmatism, constructivism, existentialism, and Pancasila national education. There are 4 learning models discussed, namely: Scientific Model, Problem Based Learning, Discovery Learning, and Project-Based Learning